Challenges in Teaching Arabic to Early Childhood Learners: Pedagogical and Psycholinguistic Perspectives: Tantangan dalam Pengajaran Bahasa Arab kepada Peserta Didik Usia Dini: Perspektif Pedagogis dan Psikolinguistik - Arum Rahmatika; Isop Syafe'i (Pusaka Cendekia Indonesia Foundation, 2025)
This study aims to examine the challenges of teaching Arabic to young learners at the elementary school level from pedagogical and psycholinguistic perspectives. The research employs a library research method combined with content analysis of relevant literature on Arabic language teaching, pedagogy, and psycholinguistics. The findings reveal that the challenges can be classified into two main dimensions. From a pedagogical perspective, the major issues include overloaded curricula, monotonous traditional methods, limited teacher competence, and the lack of interactive learning media. From a psycholinguistic perspective, the challenges involve children’s cognitive development, low motivation, mother tongue interference, and language anxiety. The discussion emphasizes the need for an integrative approach that combines pedagogical and psycholinguistic strategies, such as curriculum redesign, communicative teaching methods, digital technology integration, and the creation of enjoyable learning environments. The study concludes that the effectiveness of Arabic language learning at the elementary level can be improved by aligning cognitive, affective, and social aspects of learners Penelitian ini bertujuan untuk mengkaji problematika pengajaran bahasa Arab pada anak usia dasar dengan menggunakan perspektif pedagogis dan psikolinguistik. Metode penelitian yang digunakan adalah studi pustaka (library research) dengan analisis isi terhadap literatur terkait pengajaran bahasa Arab, teori pedagogi, dan psikolinguistik. Hasil penelitian menunjukkan bahwa problematika pembelajaran mencakup dua dimensi utama. Dari sisi pedagogis, kendala utama meliputi kurikulum yang padat, metode tradisional yang membosankan, keterbatasan kompetensi guru, serta kurangnya media pembelajaran interaktif. Dari sisi psikolinguistik, tantangan mencakup perkembangan kognitif anak, rendahnya motivasi, interferensi bahasa ibu, serta kecemasan berbahasa. Diskusi lebih lanjut menegaskan perlunya pendekatan integratif yang menggabungkan strategi pedagogis dan psikolinguistik, seperti redesain kurikulum, penggunaan metode komunikatif, pemanfaatan teknologi digital, dan penciptaan lingkungan belajar yang menyenangkan. Penelitian ini menyimpulkan bahwa efektivitas pembelajaran bahasa Arab pada anak usia dasar dapat ditingkatkan dengan memperhatikan keselarasan antara aspek kognitif, afektif, dan sosial siswa.